Music - Nicholas Cook (Oxford University Press, 2000)
This very short introduction, written with both humor and flair, begins with a sampling of music as human activity and then goes on to consider the slippery phenomenon of how music has become an object of thought. Covering not only Western and classical music, Cook touches on all types from rock to Indonesian music and beyond. Incorporating musical forms from every continent, Music will make enjoyable reading for beginner and expert alike